A note on intra-industry foreign direct investment - J.H. DUNNING (PSL Quarterly Review, 2013)
This note suggests that patterns of international direct investment in manufacturing industry not only tend to follow those of commodity trade, but that, over the years 1965-1975, the intra-industry component of such investment had tended to increase. However, there are only a few countries in the world which are both substantial inward and outward direct investors. Nevertheless, data on outward and inward direct investment assets in five countries over this 10 year period reveal some interesting insights.